The Role of Meteorin-Like Peptide and TRPM2 in Differential Diagnosis in Benign, Premalignant and Malignant Lesions of the Endometrium - Balta, Hılal; Kocaman, Nevin (My University, 2023)
Objective: Endometrial cancer is the most common gynecological cancer in developed countries, and Type 1 endometrial adenocarcinoma develops from the background of atypical hyperplasia. Early diagnosis is effective on mortality and morbidity, and immunohistochemical biomarkers are the most helpful diagnostic method. Materials and Methods: The samples of this retrospective study were obtained from the pathology laboratory of the Fırat University, School of Medicine, Department of Pathology. A total of 60 patient samples were used, with 10 samples in each group. The cases of proliferative endometrium, simple endometrial hyperplasia without atypia, simple atypical endometrial hyperplasia, complex endometrial hyperplasia without atypia, complex atypical endometrial hyperplasia, and endometrial endometrioid adenocarcinoma were included in the study. The tissue samples were treated and evaluated with Meteorin-like peptide (METRNL) and TRPM2 in all groups. Results: Statistically significant relationships were detected between endometrial hyperplasia without complex atypia, endometrial hyperplasia with complex atypia, and Type-1 endometrial adenocarcinoma in terms of METRNL and TRPM2 immunoreactivity. Conclusion: The study results support the presence of a significant association in terms of the expression of METRNL and TRPM2 in endometrial tumors. The results of the present study confirm that both markers have diagnostic value for endometrioid carcinoma.
Keywords: Kadın Hastalıkları ve Doğum; Patoloji; Onkoloji; Biyokimya ve Moleküler Biyoloji; Tıbbi Laboratuar Teknolojisi